New detecting techniques for a future calorimetry. (13th February 2015) - Auffray, E; Buganov, O; Fedorov, A; Korjik, M; Lecoq, P; Tamulaitis, G; Tikhomirov, S; Vasil'ev, A
Abstract: In the last forty years, application of crystalline materials in homogeneous Electromagnetic Calorimeters has played a crucial role in the discovery of matter properties and promoted a continuous progress in the detecting technique. The detection systems progressed from small detectors based on NaI(Tl), CsI(Na), BaF2, PbF2, and Bi4 Ge3 O12 to giant Electromagnetic Calorimeters of CMS, ALICE Collaborations at LHC and PANDA Collaboration at FAIR, where the systems consisted of thousands lead tungstate PbWO4 scintillation crystals. Lead tungstate (PWO) became the most extensively used scintillation material in high energy physics experiments. PWO possesses a unique combination of scintillation properties including high energy and time resolutions in the detection of high energy particles. Here, we report on the results of the two photon absorption in PWO crystals obtained by pump-probe technique using ultra short laser pulses. The results demonstrate that the relaxation processes in PWO offer capability of this material to be used in detection systems to make a time stamp with precision close to 10 -12 s or even better.